Tata Kelola Penanganan Kasus COVID-19 di Selandia Baru - Pardede, Joe Putra Pratama; Rozali, Rozmita Dewi Yuniarti (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2020)
A pandemic caused by the 2019 corona virus is known as COVID-19. Corona virus (COVID-19) according to the World Health Organization (WHO) is an emerging disease caused by infection with the SARS-CoV-2 virus known as an infectious respiratory disease. New Zealand confirmed its first case on February 28. This paper is intended to know the governance of handling COVID-19 cases in New Zealand and how COVID-19 impacts. Data collection techniques taken from the type of library research (library research), is the collection of library data by taking the theme of international articles suitable for research and study. In addition, secondary data is also obtained from the official website of the New Zealand government. The results of this study can be concluded that the government implemented an elimination strategy to suppress the COVID-19 case. Lockdown has a negative impact on learning. The government also helps in the economic field. Through an elimination strategy, New Zealand successfully suppressed the spread of COVID-19. DOI : https://doi.org/10.33005/jdg.v10i2.2126